Localized immunoglobulin light chain amyloidosis: Novel insights including prognostic factors for local progression - Basset, Marco; Hummedah, Kamal; Kimmich, Christoph; Veelken, Kaya; Dittrich, Tobias; Brandelik, Simone Christine; Kreuter, Michael; Hassel, Jessica C.; Bosch, Nikolaus; Stuhlmann-Laeisz, Christiane; Blank, Norbert; Müller-Tidow, Carsten; et al. (American journal of hematology, 2020)
In localized light chain amyloidosis (locAL), amyloidogenic light chains (aLC) are produced and deposited locally by a B-cell clone. We present 293 patients with immunohistochemically confirmed locAL.